Avoiding Carbothermal Reduction: Distillation of Alkoxysilanes from Biogenic, Green, and Sustainable Sources. (3rd December 2015) - Laine, Richard M.; Furgal, Joseph C.; Doan, Phi; Pan, David; Popova, Vera; Zhang, Xingwen
Abstract: The direct depolymerization of SiO2 to distillable alkoxysilanes has been explored repeatedly without success for 85 years as an alternative to carbothermal reduction (1900 °C) to Simet, followed by treatment with ROH. We report herein the base‐catalyzed depolymerization of SiO2 with diols to form distillable spirocyclic alkoxysilanes and Si(OEt)4 . Thus, 2‐methyl‐2, 4‐pentanediol, 2, 2, 4‐trimethyl‐1, 3‐pentanediol, or ethylene glycol (EGH2 ) react with silica sources, such as rice hull ash, in the presence of NaOH (10 %) to form H2 O and distillable spirocyclic alkoxysilanes [bis(2‐methyl‐2, 4‐pentanediolato) silicate, bis(2, 2, 4‐trimethyl‐1, 3‐pentanediolato) silicate or Si(eg)2 polymer with 5–98 % conversion, as governed by surface area/crystallinity. Si(eg)2 or bis(2‐methyl‐2, 4‐pentanediolato) silicate reacted with EtOH and catalytic acid to give Si(OEt)4 in 60 % yield, thus providing inexpensive routes to high‐purity precipitated or fumed silica and compounds with single Si−C bonds.